x = (1 x 3 x 5 x ... x 1993 x 1995 x 1997) (mod 1000)
= (1 x 3 x 5 x ... x 993 x 995 x 997 x 1 x 3 x 5 x ... x 993 x 995 x 997)(mod1000)
= (1 x 3 x 5 x ... x 993 x 995 x 997)^2 (mod 1000)
= product from n=1 to n=499 (2n-1)^2 (mod 1000)
原帖由 ~HeBe~_@ 于 3-7-2008 10:07 PM 发表
x = (1 x 3 x 5 x ... x 1993 x 1995 x 1997) (mod 1000)
= (1 x 3 x 5 x ... x 993 x 995 x 997 x 1 x 3 x 5 x ... x 993 x 995 x 997)(mod1000)
= (1 x 3 x 5 x ... x 993 x 995 x 997)^2 (mod 1000)
...
请问为什么= (1 x 3 x 5 x ... x 993 x 995 x 997 x 1 x 3 x 5 x ... x 993 x 995 x 997)(mod1000)呢?为什么两次呢?